Two new Caymanostella species discovered at deep-sea wood falls in the Clarion Clipperton Fracture Zone - Magdalini Christodoulou; Christopher Mah; Pedro Martinez Arbizu (Scientific Reports)
Abstract In an era where human activities increasingly impact the deep sea and, with future ventures such as deep-sea mining on the horizon, describing deep-sea biodiversity is vital for conservation, sustainable resource management, understanding global ecological processes, and informing policy decisions. Polymetallic nodule fields, in particular, have been proven to be reservoirs of previously undiscovered biodiversity. As part of ongoing efforts to unveil this dark diversity, two new species of Caymanostella −Caymanostella persephone nov. sp. and Caymanostella hades nov. sp.,− recovered on a single piece of sunken wood in the Clarion Clipperton Fracture Zone, a region in the eastern Pacific Ocean targeted for mining, are described herein. Although both species were sampled on the same piece of wood, they are genetically distinct and can be differentiated from each other and their congeners morphologically by various morphological characters, including the arrangement of the central plates, the position of gonopores, and the form of their abactinal armaments. The discovery of the new species brings the total number within the Caymanostella genus to ten and expands the known geographical distribution of the genus.